Annexin V-containing cubosomes for targeted early detection of apoptosis in degenerative retinal tissue. Issue 46 (5th November 2018) - Ding, Yue; Chow, Seong Hoong; Liu, Guei-Sheung; Wang, Bo; Lin, Tsung-Wu; Hsu, Hsien-Yi; Duff, Anthony P.; Le Brun, Anton P.; Shen, Hsin-Hui
Abstract : ANX–PS–Phy cubosomes could be applied as a safe and robust drug delivery vehicle for targeting damaged, apoptotic cells in ocular diseases. Abstract : New drug delivery materials targeting damaged ocular tissues are of particular interest. In this work, we have formulated annexin/phosphatidylserine/phytantriol and annexin/phosphatidylserine/monoolein cubosomes based on incorporation of 1, 2-dipalmitoyl- sn-glycero -3-phospho-l -serine (PS) lipid and annexin V (ANX) protein with phytantriol (Phy) and monoolein (MO) respectively. The incorporation of ANX is important because it can be used as a diagnostic tool for in vivo apoptosis detection due to its high affinity to phosphatidylserine in the presence of Ca 2+ . We have also prepared PS–Phy and PS–MO cubosomes without ANX as a comparison, and characterized them using dynamic light scattering, cryo-TEM images and small-angle X-ray scattering, showing that PS–Phy cubosomes have greater chemical stability, and that ANX–PS–Phy cubosomes have the potential for in vivo drug delivery. In addition, we have reconstituted an apoptotic biomimetic membrane on a surface to gain insights into cubosome–bilayer interactions using a quartz-crystal microbalance and neutron reflectometry. The neutron reflectivity data reveal that there is exchange of materials between the biomimetic apoptotic bilayer and ANX–PS–Phy cubosomes, with an accumulation of ANX between the membrane and cubosomes possibly being the reason for the reduced cytotoxicity of ANX–PS–Phy cubosomes. A rat model of laser-induced choroidal neovascularization showed that ANX–PS–Phy cubosomes specifically targeted apoptotic cells in vivo . We propose that ANX–PS–Phy cubosomes are a potential candidate for ocular drug delivery for eye diseases.